Cost Analysis of Iron-Related Complications in a Single Institute - Kim, Ki Hwan (The Korean Association of Internal Medicine, 2009)
BACKGROUND/AIMS: The financial burden of caring for iron-related complications (IRCs) is an emerging medical problem in Korea, as in Western countries. We produced a preliminary estimate of the costs of treating patients for IRCs. METHODS: The medical records of patients who had received multiple transfusions were reviewed. Newly developed cardiomyopathy, heart failure, diabetes mellitus, liver cirrhosis, and liver cancer were defined as IRCs. The costs of laboratory studies, medication, oxygenation, intervention, and education were calculated using working criteria we defined. Costs that had a definite causal relationship with IRCs were included to produce as accurate an estimate as possible. RESULTS: Between 2002 and 2006, 650 patients with hematologic diseases, including 358 with acute leukemia, 102 with lymphoma, 58 with myelodysplastic syndrome or myeloproliferative disease, 46 with multiple myeloma, and 31 with chronic leukemia, received more than 10 units of red blood cells. Nine patients developed IRCs. The primary diagnoses of eight patients were aplastic anemia and that of one patient was chronic lymphocytic leukemia. Two patients who had diabetes were excluded because one was treated at another hospital and the other was diagnosed as oxymetholone-induced diabetes. Of the seven patients included, liver cirrhosis developed in two, heart failure in four, and diabetes mellitus in three. Some of them had two diagnoses. The total cost attributed to IRCs for the seven patients was 47,388,241 KRW (approximately 50,000 USD). CONCLUSIONS: The medical costs of IRCs are considerable, and more effective iron-chelating therapy is necessary to save medical resources and improve patient care. More in the way of comprehensive health and economic studies of IRCs are needed to allow both clinicians and health-policy makers to make better decisions.